2022
DOI: 10.1039/d2nr01300b
|View full text |Cite
|
Sign up to set email alerts
|

A theory of skyrmion crystal formation

Abstract: A generic theory about skyrmion crystal (SkX) formation in chiral magnetic thin films and its fascinating thermodynamic behaviours is presented. A chiral magnetic film can have many metastable states with...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…[165] The nature of skyrmion entropy is also an interesting issue. [165,166] Moreover, skyrmion qubits can be constructed by using the energy-level quantization of the helicity degree of freedom. [167] Quantum computing using chiral spin textures is worth of exploring further.…”
Section: Discussionmentioning
confidence: 99%
“…[165] The nature of skyrmion entropy is also an interesting issue. [165,166] Moreover, skyrmion qubits can be constructed by using the energy-level quantization of the helicity degree of freedom. [167] Quantum computing using chiral spin textures is worth of exploring further.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the stripe skyrmion structure follows m z ( x ) = for – L /2 < x < L /2 and m z ( x ) = for L /2 < x < 3 L /2, where L and w are the stripe width and wall thickness. x = 0 refers to stripe center where m z = 1.…”
mentioning
confidence: 98%
“…Testing this belief motivates current study. For a perpendicularly magnetized chiral film described by magnetization M , the Heisenberg exchange stiffness constant A , anisotropic coefficient K , and the Dzyaloshinskii–Moriya interaction (DMI) coefficient D , κ ≡ (π 2 D 2 )/(16 AK ) = 1, an important quantity, separates isolated skyrmions (κ < 1) from condensed stripe skyrmions (κ > 1) in the absence of a magnetic field. In this Letter, we study how the morphology of a collection of stripe skyrmions changes as the stripe widths gradually increase. Our results show the topological equivalence of stripy states and SkXs and raise the question about the notion of the first-order phase transition in SkX formations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic moments in these multi-q structures can be noncollinear and noncoplanar. In general, multi-q has also been used to define the spin texture as superpositions of multiple spin helices or spin density waves, mostly incommensurate, such as skyrmions [33][34][35][36][37][38][39][40][41][42] in 2D thin films or layered structures, and hedgehog 43,44 in 3D structures, with a real space non-trivial topology and also a periodicity much larger than the underlying crystal lattice. Although magnetic space groups (MSG) give all the symmetry operations for Wyckoff positions with breaking time-reversal symmetry due to magnetism, multi-q as a superposition of multiple propagating vectors can include the orientation of the magnetic moments to describe both commensurate and incommensurate magnetic structures with noncollinear and noncoplanar components.…”
mentioning
confidence: 99%